Intestinal injury and gut permeability in sickle cell disease - Dibyendu Dutta (Journal of Translational Medicine, 2019)
Abstract Background Due to recurrent hypoxia-reperfusion injury induced by vaso-occlusive crises (VOC), patients with sickle cell disease (SCD) may have intestinal injury and increased permeability. These may explain the qualitative and quantitative neutrophil abnormalities observed in these patients. Methods Serum intestinal fatty-acid binding protein (iFABP), lipopolysaccharides (LPS), and CD62L were measured by ELISA. Multicolor flow cytometry was used to measure circulating aged neutrophils. Results Compared to controls, SCD individuals had higher iFABP (median: 1.38 ng/ml vs 0.81 ng/ml; p = 0.04) and LPS (median: 2.15 μg/ml vs 0.69 μg/ml; p = 0.03), indicating intestinal injury and increased intestinal bacterial translocation into the systemic circulation. They also had higher soluble CD62L (median: 1.38 μg/ml vs 1.11 μg/ml; p = 0.04). Among SCD individuals, soluble CD62L correlated positively with circulating aged neutrophils (R = 0.7, p = 0.03) and LPS (R = 0.66, p = 0.027). Surprisingly, serum iFABP in SCD correlated negatively with both LPS (R = − 0.7, p = 0.02) and soluble CD62L (R = − 0.56, p = 0.08). Conclusions Since LPS translocation across the intestinal barrier may be due to increases in the intestinal bacterial density, gut permeability, or both, the negative correlations between iFABP and LPS, and CD62L raise the possibility that any damage-associated molecular patterns induced by intestinal injury may modulate the degree of bacterial translocation. Our results provide the first evidence of the presence of intestinal injury and increased gut permeability in SCD.